The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/2396987320984003
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-6, C-reactive protein, fibrinogen, and risk of recurrence after ischaemic stroke: Systematic review and meta-analysis

Abstract: Background Recent randomised trials showed benefit for anti-inflammatory therapies in coronary disease but excluded stroke. The prognostic value of blood inflammatory markers after stroke is uncertain and guidelines do not recommend their routine measurement for risk stratification. Methods We performed a systematic review and meta-analysis of studies investigating the association of C-reactive protein (CRP), interleukin-6 (IL-6) and fibrinogen and risk of recurrent stroke or major vascular events (MVEs). We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 65 publications
6
49
0
1
Order By: Relevance
“…Furthermore, our study found a significantly increased risk of recurrent stroke in those with a "high" CRP versus those with a "low" hsCRP, a cut-off which could be used to select higher risk patients for inclusion in clinical trials. This is supported by a recent systematic review and meta-analysis, which showed an association between increasing CRP and future risk of major vascular events in stroke survivors [25].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, our study found a significantly increased risk of recurrent stroke in those with a "high" CRP versus those with a "low" hsCRP, a cut-off which could be used to select higher risk patients for inclusion in clinical trials. This is supported by a recent systematic review and meta-analysis, which showed an association between increasing CRP and future risk of major vascular events in stroke survivors [25].…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, our findings suggest that patients with a CRP >2 mg/dL are at higher risk of recurrent stroke at 90 days, a cut-off which may be of benefit for the selection of patients for clinical trials of anti-inflammatory medications for stroke prevention. A recent systematic review suggested associations between inflammatory markers with recurrent stroke [25]. A Cochrane systematic review did not identify any studies examining the use of anti-inflammatory medications in the prevention of recurrent stroke or major cardiovascular events in patients with previous minor stroke or TIA [32].…”
Section: Discussionmentioning
confidence: 99%
“…insight into the examined relationship. 44 The results from these meta-analyses, when seen together with Mendelian randomization results supporting associations between lifetime genetically downregulated IL-6 signaling and lower ischemic stroke risk, 12 provide further support in favor of IL-6 signaling as a promising target for lowering stroke risk. An interesting finding from our analysis is the clearly loglinear dose-response relationship between IL-6 levels and stroke risk.…”
Section: Discussionmentioning
confidence: 78%
“…4 After a first stroke, studies of inflammatory markers have reported inconsistent associations with recurrent stroke, in part, relating to differing methods and analytic techniques. 5 However, several have reported that CRP and other inflammatory biomarkers are associated with stroke recurrence across all stroke subtypes, including large artery disease, lacunar stroke, and with thromboembolism in atrial fibrillation. 5 In patients with carotid stenosis, high density of inflammatory cells in excised plaque is associated with plaque instability and early stroke recurrence, 6 while positron emission tomography imaging studies have found that plaque inflammation is associated with early recurrent stroke independent of stenosis severity.…”
Section: See Related Article P 2827mentioning
confidence: 99%